PENGARUH KONSENTRASI DAN WAKTU INKUBASI EM4 TERHADAP KUALITAS KIMIA KOMPOS - Siburian, R. (Bumi Lestari; Vol 8 No 1 (2008))
The effects of consentrations and incubations periods EM4 on the chemical quality of compost have been done. The aim of the research was to study the effects of consentrations and incubations periods on the content of N, P, and K. The methods were analysed by using titration, spectrofotometry UV-VIS and flame phototmetry. The result of the research was analysed by group randomized design with two factors. The result of the research showed that the consentrations and incubation periods had the significant effect on the content of N, P, and K and the interaction between consentrations and incubation periods of EM4 the quality of compost. The optimal condition to content N, P, and K of compost to consentrations and incubation periods is 2,5% and 20 days, 25% and 20 days; 25% and 35 days respectively